COMPENSATORY AND SUSCEPTIVE RESPONSES OF COWPEA GENOTYPES TO INFESTATION BY APHIS CRACCIVORA KOCH. (Journal of Science and Technology, 2016)
The aim of the study was to estimate yield loss to10 selected genotypes of cowpea as a result of Aphis craccivora infestation during the vegetative phase of the crop. There were two trials with four replications. The first trial serving as the control was sprayed at the seedling, flowering and podding stages against insect pests with lambda cyhalothrin (PAWA ®). The other trial was sprayed only at flowering and podding stages.  The cowpea seedlings of the second trial were infested with five four-day-old aphids per seedling two weeks after planting. The aphids were allowed to form colonies and fed on the seedlings until symptoms of damage were observed. When the susceptible seedlings became stunted with distorted leaves and yellowing of leaves at two weeks after infestation (28 days after planting), aphids were controlled. The results showed that aphids’ infestation delayed flowering and maturity of genotypes of cowpea. With the excep- tion of early flowering genotypes all the medium to late flowering genotypes produced higher dry grain yield in infested plots than the control plots. The trend was not different from the produc- tion of dry biomass. The results of the present study implies that control of aphids infestation in early maturing cowpea genotypes should not be delayed up to two weeks after infestation or 28 days after planting. Aphid’s infestation period for studies in susceptive response in medium to late maturing genotypes should go beyond 28 days after planting probably up to 35 days after planting.